Equilibrium blocking in large quasilinear economies - Yusuke Kamishiro; Roberto Serrano (Brown University, Department of Economics, 2009)
We study information transmission in large interim quasilinear economies using the theory of the core. We concentrate on the core with respect to equilibrium blocking, a core notion in which information is transmitted endogenously within coalitions, as blocking can be understood as an equilibrium of a communication mechanism used by players in coalitions. We consider independent, ex-post and signal-based replicas of the basic economy. For each, we offer an array of negative and positive convergence results as a function of the complexity of the mechanisms used by coalitions. We identify conditions under which asymmetric information remains as an externality and non-market outcomes stay in the core, as well as those for the core to converge to the set of incentive compatible ex-post Walrasian allocations. Further, all the results are robust to the relaxation of the incentive constraints, and hence suggest a process through which information may get incorporated into a fully revealing equilibrium price function.
Keywords: C71; C72; D51; D82; 330; Core w.r.t. Equilibrium Blocking; Core Convergence; Independent Replicas; Ex-Post Replicas; Signal-Based Replicas; Information Transmission; Communication Mechanisms; Mediation; Rational Expectations Equilibrium